BIBLIOMETRIX PEMBELAJARAN BAHASA DI SEKOLAH DASAR - Asip, Muhammad; Likus, Likus; Dirhan, Dirhan; Wisataone, Voettie (Institut Daarul Qur'an Jakarta, Indonesia, 2022)
This study aims to see the development of research on language learning in elementary schools. This type of research is included in the type of literature review research. Research data sourced from Scopus. In the Scopus search column, data was found as many as 1,357,373 articles. The data was selected in four stages, namely identification, screening, eligibility, and included so that 26 articles were obtained for data processing. The process of interpreting the data is carried out with the help of R studio type 386.4.1.3. The results obtained are data with three categories of research information, namely authors, document searches, and documents. Based on the results of the study, it can be concluded that language learning in elementary schools is growing rapidly in the USA and the United Kingdom. Meanwhile, the most popular place to publish language learning articles is the journal of speech. For popular vocabulary in research, namely learning and linguistics